Expansão térmica de nanotubos de carbono de duas camadas - Guarnetti, Leandro Jose [UNESP] (2014)
The special properties of carbon nanotubes (NTs) have inspired researchers in many technological applications. Examples of macroscopic products that contain or are made of CNTs are tennis rackets, baseball bats, bicycle frames, ligthweiht wind turbine blades and boat hulls. In order to get more knowledge about the behavior of these products and materials, either to develop new applications or improve the actual ones, it is important to investigate the physical properties of individual CNTs in diverse situations. In this work, using tools of molecular dynamics simulations, we present three results for the coefficient of thermal expansion of the Double Walled CNTs (DWCNTs) (5.5)@(10,10) with and without defects. The types of defects considered here are carbon atoms at interstitial sites and sp connections between the walls of the (5,5)@(10,10) DWCNT. Our methods are, first, validate by the calculation of the coefficient of thermal expansion of the Single Walled CNT (SWCNT) (10,10) and the camparison of the result with that from the literature. We show that the coefficient of thermal expansion of the (5,5)@(10,10) DWCNT. This result is discussed in terms of the coefficient of thermal expansion of the diamond